Ravulizumab v léčbě pacientů s AQP4-IgGpoz neuromyelitis optica a onemocněním jejího širšího spektra - Nytrová, Petra; Menkyová, Ingrid (Neurologie pro praxi, 2024)
Ravulizumab is a humanized monoclonal antibody targeting the complement C5 protein. This drug has been approved by different regulatory agencies worldwide for the treatment of AQP-4 seropositive NMOSD based on the results of the CHAMPION-NMOSD trial. Similar to eculizumab, ravulizumab offers highly effective prevention of NMOSD relapses. Both molecules demonstrated more than 90% reduction in relapse risk compared to the placebo group. Ravulizumab has a longer half-life allowing extending interval dosing from two to eight weeks compared to eculizumab. Patients taking C5 complement inhibitors have an increased risk of serious meningococcal infections, therefore vaccination is mandatory before treatment initiation.
Keywords: Clinical Studies as Topic; komplement C5; Aquaporin 4; Complement C5; Ravulizumab; lidé; AQP4-IgG pozitivní NMOSD; neuromyelitis optica; Meningococcal Infections; meningokokové infekce; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; Neuromyelitis Optica; studie CHAMPION-NMOSD; klinická studie jako téma; Humans; akvaporin 4